Formation of the creative potential of students of the of vuz (institute of higher education) of cultural - Vera A. Кurina; Elena G. Protsenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In this article the problem of creative potential of students of higher educational institution of culture as future specialists of the social and cultural sphere is actualized. In this regard, the clarification of the basic concepts of the problem. The authors analyze the methodological foundations of the formation of creative potential, as the modern world requires graduates of universities of culture readiness to creatively and productively solve emerging professional problems. The hypothesis of the study is that the use of such methods as creative project, role-playing games, training in the learning process can maximize the development of students' abilities and contribute to the formation of their creative potential. The organization of such training allows to diversify professional training of students. The main problem of this article is connected with the fact that, despite the existing methods of creative potential formation, the level of its formation remains extremely low; not all modern methods in teaching serve the needs of the student. The paper presents one of the possible solutions to this problem on the example of the methodology of classes on the developed course in the discipline "History of arts: history of cinema" with students of the University of culture of the direction of training 51.03.03 Socio-cultural activities. The features of the organization of classes, performance of practical tasks by students, a variety of used forms, methods and means of training, contributing to the formation of creative potential of students. The results of the work and the results obtained at the end of training in the discipline "Istria of arts: the History of cinema"are summed up. The authors identified the main approaches to the organization of classes (system, personality-oriented, competence-based, interdisciplinary). The paper emphasizes the importance of creating conditions for creative activity.